A Legal Debate on Polygamy: Classical and Contemporary Perspectives - Sukring Syamsuddin (UIN Sunan Kalijaga Yogyakarta, 2018)
The Islamic texts concerning polygamy in the Qur’an, Hadith, and other sources are still in the state of mujmal which have no strict indication to the precise meaning and instruction. The argument can be debated in multi- interpretation frame. In practice, a lot of muslims tend to generalize the application of law of polygamy. It becomes an interesting issue for some Indonesian muslim due to its close relation to the tendency or desire of men to add his wife. Some of them even believe polygamy as one of the Prophetic way (sunnah). This view can historically be refuted, considering that the Prophet did polygamy after Khadījah, his first wife, died. Another fact is that all of the Prophet’s wives are widows whose husbands died in the battlefield, except ‘Aisyah. In addition, the marriage of the Prophet with these women is a part of the God’s special order. In this case, polygamy is an exclusivity for the Prophet and it cannot be viewed as the Prophetic wagons to be applied by his followers. Here there is a difference in the perspective of classical and contemporary Muslim scholars concerning the issue based on their different views on the word of God in QS. al-Nisa’ (4): 3. In principle, the Qur’an allows but does not advocate polygamy. It is in this perspective that some scholars are divided into those who absolutely allow, allow in emergency, those who have moderate understanding, and some who are strict to be conservative, based on their different analytical and methodological issues.[Nash tentang poligami di dalam al-Qur'an, as-Sunnah dan sumber-sumber lain, sifatnya masih umum (mujmal). Dalilnya bisa diperdebatkan dengan multi tafsir, sehingga dalam praktiknya orang menggunakan hukum poligami secara